Comparative Effectiveness of Structural versus Regulatory Protein Gene Transfer on Articular Chondrocyte Matrix Gene Expression. (January 2019) - Shi, Shuiliang; Wang, Congrong; Chan, Albert; Kirmani, Kashif; Eckert, George J.; Trippel, Stephen B.
Objective: The production of extracellular matrix is a necessary component of articular cartilage repair. Gene transfer is a promising method to improve matrix biosynthesis by articular chondrocytes. Gene transfer may employ transgenes encoding regulatory factors that stimulate the production of matrix proteins, or may employ transgenes that encode the proteins themselves. The objective of this study was to determine which of these 2 approaches would be the better choice for further development. We compared these 2 approaches using the transgenes encoding the structural matrix proteins, aggrecan or type II collagen, and the transgene encoding the anabolic factor, insulin-like growth factor I (IGF-I). Methods: We transfected adult bovine articular chondrocytes with constructs encoding type II collagen, aggrecan, or IGF-I, and measured the expression of type II collagen ( COL2A1 ) and aggrecan ( ACAN ) from their native genes and from their transgenes. Results: IGF-I gene ( IGF1 ) transfer increased the expression of the native chondrocyte COL2A1 and ACAN genes 2.4 and 2.9 times control, respectively. COL2A1 gene transfer did not significantly increase COL2A1 transcripts, even when the transgene included the genomic COL2A1 regulatory sequences stimulated by chondrogenic growth factors. In contrast, ACAN gene transfer increased ACAN transcripts up to 3.4 times control levels. IGF1, but not ACAN, gene transfer increased aggrecan protein production. Conclusion: Taken together, these results suggest that the type II collagen and aggrecan production required for articular cartilage repair will be more effectively achieved by genes that encode anabolic regulatory factors than by genes that encode the matrix molecules themselves.